Managing Solid Waste In School Environment Through Composting Approach - Mpuangnan, Kofi Nkonkonya; Mhlongo, Hlengiwe Romualda; Govender, Samantha (Journal of Integrated Elementary Education, 2023)
This study aimed at improving solid waste disposal in schools by using the composting approach. The theory that underpinned this study was Reduce, Reuse, and Recycle (3R) theory, while the necessary data were gathered by using a synthesis and integration approach. The following three research questions were framed to guide the conduct of the study: How important is solid waste management in schools? What pedagogical techniques are most effective for promoting environmental sustainability by teaching composting in schools? What are the challenges involved in the composting process at school?  The synthesis and integration approach assisted in integrating concepts from different sources and synthesizing those concepts to create a comprehensive and cogent argument in accordance with emerging themes. It was discovered that solid waste management in schools was particularly crucial since schools produced a lot of rubbish and that waste may affect the environment negatively. Composting is essential to improve school solid waste because it enhances soil health, decreases waste, and encourages sustainable agricultural methods. Three pedagogical techniques that could be utilized to facilitate the teaching and learning of composting in schools have evolved based on the theoretical framework and the literature provided. Project-based learning (PBL), hands-on learning, and inquiry-based learning were some of the new pedagogical strategies. However, some of the challenges with the composting process were identified as follows: difficulty in regulating the moisture level of the compost, keeping the proper balance of carbon and nitrogen in the compost pile, and inability to educate students and staff about the composting process.